Robert Browning’s Poem Porphyria’s Lover: Viewed from the Perspective of a Short Story - Arafat, Faisal (International Journal of Language and Literary Studies, 2021)
Robert Browning quite as an exception to his contemporary Victorian poets opted for the psychoanalysis of his characters in his poems. His obsession of delving deeper into the psyche of his characters most often lent his poems with the essence and atmosphere of a story, to be more accurate – a short story. Browning’s readers still today hovers in the labyrinth created in his poetic world. He leaves his readers in such a juncture from where the readers time and again look back into the plot of his poems to find answers of the mysteries invested by the poet. Stylistically being much ahead of the contemporary trend of poetry, Browning’s poems could be labeled as futuristic. His artistic faculty in his poems can only be somewhat explained and understood if analyzed from the perspectives of a short story. Only then the crossroads where Browning leaves his readers in his poems can find a destination and provide a literary solution. One of the most extraordinary poems of Robert Browning is ‘Porphyria’s Lover’. This paper is an analysis of the poem from the perspective of the features of a short story. The plot and theme of the poem is quite obscure especially the ending of the poem leaves the readers with a feeling of puzzle and incompleteness. In order to explain this puzzle and incompleteness this study presents an elaborate discussion of the characteristics of short story. Then it discusses the storytelling ability of Browning in his poems and finally based on the findings presents an analysis of the poem to determine the matching characteristics of a short story in the poem. The study is completely based on a qualitative analysis.